A Study on Rural Retailer and Consumer Decision Making - A Literature Review - Samira Nuzhat; Md. Mamun Habib (ExcelingTech, 2023)
Abstract— The aim of this study is to explore the role of rural retailers and examine how they influence rural consumer’s purchase behaviour. Also, how as a part of unorganized retailing, the rural retailer represents his unique characteristics was investigated. The parameters of their merchandising, their advantages of social capital, vulnerability and drawbacks of rural retailer’s remoteness was revisited too. This article took a consolidative literature review method where secondary information and data were collected. Numerous journals, research article, publications written on rural retailers were collected, analysed and evaluated. Renowned database and search engines like Google scholar, Elsevier, Emerald, and JSTOR were reviewed for collecting relevant journal articles and research papers. This study later presented a synthesized discussion on how as a vital link of the urban to rural supply chain, rural retailers act as a ‘lifeline’ of daily necessities. The realities that contributes to their success and failures are discussed as well. Subsequently, as the rural retailers have a very important role to play in the developing economy, the unmistakable need of further, in-depth research on them became very evident.